Early Vitamin K Deficiency Bleeding in a Neonate Associated with Maternal Acute Fatty Liver of Pregnancy - Shreyas Arya; Carol J. Richardson; Sunil Jain; Leonard E. Swischuck (Thieme Medical Publishers, Inc., 2015)
Abstract Introduction Acute fatty liver of pregnancy (AFLP) is a rare but potentially fatal condition occurring in the third trimester or early postpartum period. It is characterized by microvesicular fatty infiltration of the liver. Clinically, the three most prominent derangements in women with AFLP are hepatic dysfunction, renal insufficiency, and impaired coagulation. AFLP is associated with an increased incidence of morbidity and mortality in neonates, though the exact cause for this remains unclear. Deficiency of vitamin K in patients with liver disease has been widely reported. Case Description We present a unique case of severe intracranial bleeding because of the early vitamin K deficiency in a neonate whose mother had AFLP along with accompanying renal insufficiency. Conclusion We suggest that monitoring infants born to mothers with AFLP, for vitamin K deficiency bleeding will help reduce morbidity and mortality in these infants.